Comparison of Dexmedetomidine and Fentanyl for Blunting Hemodynamic Response to Intubation - Khan, Abid; Feroz, Shizan Hamid; Iqbal, Sana; Khan, Zafarullah; Yaseen, Talha; Khan, Shahum (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the effects of Dexmedetomidine and Fentanyl on the blunting of the hemodynamic response to intubation.Study Design: Comparative cross-sectional study.Place and Duration of Study: Combined Military Hospital Peshawar Pakistan, from Jan to Aug 2021.Methodology: This study was conducted on 908 patients who were ASA grades I and II and underwent general anaesthesia for any surgical procedure. Group-A received Dexmedetomidine, while Group-B received Fentanyl and routine preanaesthetic medications. Hemodynamic responses in both groups were recorded and compared in heart rate and mean arterial pressure at baseline, 2, 5, and 10 minutes after the intubation.Results: Out of 908 patients equally divided into two groups, 579 (63.7%) were males, while 329 (36.3%) were females. The mean age of patients included in our study was 33.445 6.363 years. A significant increase in heart rate was found at 2, 5 and 10 minutes in the group who took Fentanyl compared to the group who took Dexmedetomidine (p-value 0.001).  ignificant increases in mean arterial pressure were found at 2 and 5 minutes (p-value 0.019 and 0.007, respectively) in the Fentanylgroup, while no significant difference was found at 10 minutes in either group (p-value 0.914).Conclusion: In this study, Dexmedetomidine was found to be a better agent in providing hemodynamic stability during and after the process of intubation compared to Fentanyl.